iTRAQ-based quantitative proteome analysis in liver of large yellow croaker Larimichthys crocea under high temperature stress - Xiaoying Zhang; Man Jiang; Xiaofang Cai; Jing Zhang; Longshan Lin; Xiande Liu (Aquaculture Reports, 2023)
In order to explore the changes in protein expression of large yellow croaker Larimichthys crocea under high temperature stress, isobaric tags for relative and absolute quantitation (iTRAQ) combined with liquid chromatography-tandem mass spectrometry (LC-MS/MS) was used to perform proteome analysis on the liver between thermal-tolerant and thermal-sensitive groups of large yellow croaker. A total of 23,269 peptides and 3,388 proteins were identified, and 442 differentially expressed proteins (DEPs) were screened, among which 171 proteins were up-regulated and 271 proteins were down-regulated with fold change ≥ 1.2 or < 0.83 and P < 0.05 as the standard. Twelve randomly selected proteins were verified by PRM and four proteins were verified by Western blot, and the results were consistent with the results of iTRAQ quantitative proteome analysis. Through bioinformatics analysis, DEPs mainly enriched in GO terms such as translation, electron transport chain, ribosome, NADH dehydrogenase activity, and KEGG pathways such as protein processing in endoplasmic reticulum, ribosomes, oxidative phosphorylation, steroid biosynthesis, and biosynthesis of unsaturated fatty acid. In summary, high temperature stress had significant effect on protein synthesis, energy metabolism and lipid metabolism in liver of large yellow croaker, the protein synthesis had decreased, energy metabolism changed from oxidative phosphorylation to glycolysis, and fatty acid biosynthesis increased and fatty acid metabolism decreased in thermal-tolerant group of large yellow croaker. The results will help to study molecular regulatory mechanisms of thermal adaptation in large yellow croaker.